Yorkshire West Riding : Sheffield and the South / by Ruth Harman and Nikolaus Pevsner ; with contributions from Roger Harper [and 5 others]. - Pevsner, Nikolaus, 1902-1983. (Buildings of England, 2017)
This authoritative guide, the companion to 'Yorkshire West Riding: Leeds, Bradford and the North', covers a vast area marked by tremendous diversity of both landscape and buildings. The territory is rich in medieval churches and castles, 17th-century houses and 18th-century mansions, yet it is also deservedly famous for its outstanding 19th- and 20th-century ecclesiastical, civic, commercial and industrial buildings. Major examples of every period of English architecture are represented, from Selby Abbey to the palatial country house of the Earls Fitzwilliam at Wentworth Woodhouse, and from Halifax Town Hall to Sheffield's Park Hill flats and the Yorkshire Sculpture Park near Wakefield. In the fine Pevsner tradition, this book situates the region's full array of buildings within geological, local, national, and international contexts.